Clinicopathological characteristics and prognosis of stage IV colorectal cancer - MIYOSHI, NORIKATSU (Mol Clin Oncol, 2015)
The aim of this study was to determine the role of curative resection in metastatic colorectal cancer (CRC) and determine the subset of patients who may benefit from concurrent curative resection of primary and metastatic lesions. A total of 103 patients diagnosed with synchronous liver and/or lung metastatic CRC at the Osaka Medical Center for Cancer and Cardiovascular Diseases between 1983 and 2010 were retrospectively investigated. All the patients underwent curative resection of the primary and metastatic lesions. The median follow-up time was 5.69 years. A total of 83 and 13 patients had only liver or lung metastasis, respectively, whereas 7 patients had synchronous liver and lung metastases. A total of 25 patients (24.2%) had no recurrence following curative resection and 14 patients (13.5%) received more than one re-resection for disease recurrence and survived without any further recurrence thereafter. The 5-year survival of liver or lung metastatic CRC was 43.7 or 90.0%, respectively. However, the median overall survival (OS) in patients with synchronous liver and lung metastases was 20.7 months. In the univariate and multivariate analyses, tumour invasion, synchronous liver and lung metastases and time-to-recurrence after the first curative resection were significantly associated with OS and disease-free survival. In conclusion, curative resection confers longer-term survival in patients with liver or lung metastatic CRC.